(untitled) (Research, Society and Development, 2022)
This article aimed to analyze the relationships between Environmental Education and the connections with the various modalities of art, mirrored in art and artists, issues focused on the tripod nature/art/environmental education, seeking the meaning of artistic and creative processes, interconnected with the socio-environmental process. From this perspective, projects and artists are being discussed that use the resource of art for the stage of socio-environmental reflections. The research was developed in a qualitative perspective using bibliographic studies, interviews and analysis of documents and works by different artists as object and study. From this research, it is understood that discussing environmental issues from the perspective of art is to deal with the way people are structurally organized in society and, thus, deal with their culture and their relationships with other cultures, with how they relate to others. other human beings and the environment in which they live, As main theoretical references, authors and artists have become viable the bonds that strengthen the art/nature/environmental education partnerships, such as LISBON, PIVATO, MUNIZ among other scholars in the area.